Flood Vulnerability, Land Use Relationship and Topographic Information Assessment in Ibadan, Oyo State Nigeria - Adewuyi, Kehinde Gbola (Geoplanning: Journal of Geomatics and Planning, 2019)
This study assesses the flood Vulnerability, land use relationship and Topographic Information of Ibadan Metropolis consisting of eleven local Government areas namely; Ibadan North, Ibadan North East, Ibadan North West, Ibadan Southeast, Ibadan Southwest, Akinyele, Egbeda, Ido, Lagelu, Ona-Ara and Oluyole of Oyo State, Nigeria using geospatial analysis with the objective of analysing the areas vulnerable to flood, land cuse/land cover, determine the topography of water flow and identifying the water shed of Ibadan...............